Exosomes Recovered From the Plasma of COVID-19 Patients Expose SARS-CoV-2 Spike-Derived Fragments and Contribute to the Adaptive Immune Response - Pesce, Elisa; Manfrini, Nicola; Cordiglieri, Chiara; Santi, Spartaco; Bandera, Alessandra; Gobbini, Andrea; Gruarin, Paola; Favalli, Andrea; Bombaci, Mauro; Cuomo, Alessandro; Collino, Federica; Cricrì, Giulia; et al. (Frontiers in immunology, 2022)
Coronavirus disease 2019 (COVID-19) is an infectious disease caused by beta-coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that has rapidly spread across the globe starting from February 2020. It is well established that during viral infection, extracellular vesicles become delivery/presenting vectors of viral material. However, studies regarding extracellular vesicle function in COVID-19 pathology are still scanty. Here, we performed a comparative study on exosomes recovered from the plasma of either MILD or SEVERE COVID-19 patients. We show that although both types of vesicles efficiently display SARS-CoV-2 spike-derived peptides and carry immunomodulatory molecules, only those of MILD patients are capable of efficiently regulating antigen-specific CD4 + T-cell responses. Accordingly, by mass spectrometry, we show that the proteome of exosomes of MILD patients correlates with a proper functioning of the immune system, while that of SEVERE patients is associated with increased and chronic inflammation. Overall, we show that exosomes recovered from the plasma of COVID-19 patients possess SARS-CoV-2-derived protein material, have an active role in enhancing the immune response, and possess a cargo that reflects the pathological state of patients in the acute phase of the disease.